Arsenic speciation in rice samples for trace level determination by high performance liquid chromatography-inductively coupled plasma-mass spectrometry - Kara, Semih; Chormey, Dotse Selali; Saygilar, Ahmet; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2021)
Six arsenic species, namely arsenite (AsIII), arsenate (AsV), monomethylarsonic acid (MMA), dimethylarsinic acid (DMA), arsenobetaine (AsB) and arsenocholine (AsC) were speciated using a combination of highperformance liquid chromatography and inductively coupled plasma mass spectrometry (HPLC-ICP-MS). Under optimum chromatographic conditions, six arsenic species were well separated, and the performance of the combined system (HPLC-ICP-MS) for the species was determined. The limits of detection were calculated in the range of 0.14-0.29 ng/mL, and the corresponding quantification limits ranged between 0.45 and 0.97 ng mL-1 for the species. Spike recovery experiments performed on rice samples were used to validate the method's applicability to complex matrices. The recovery results calculated ranged between 93 and 109%, validating the method's applicability. Triplicate measurements for all spiked samples recorded percent relative standard deviation values below 10%.
Keywords: Arsenate; Arsenic; Arsenite; HPLC-ICP-MS; Speciation; ICP-MS; EXPOSURE; HEALTH; KOREA; WATER; Chemistry; Food Science & Technology; Nutrition & Dietetics